An ERAD‐independent role for rhomboid pseudoprotease Dfm1 in mediating sphingolipid homeostasis. (9th November 2022) - Bhaduri, Satarupa; Aguayo, Analine; Ohno, Yusuke; Proietto, Marco; Jung, Jasmine; Wang, Isabel; Kandel, Rachel; Singh, Narinderbir; Ibrahim, Ikran; Fulzele, Amit; Bennett, Eric J; Kihara, Akio; et al.
Abstract: Nearly one‐third of nascent proteins are initially targeted to the endoplasmic reticulum (ER), where they are correctly folded and assembled before being delivered to their final cellular destinations. To prevent the accumulation of misfolded membrane proteins, ER‐associated degradation (ERAD) removes these client proteins from the ER membrane to the cytosol in a process known as retrotranslocation. Our previous work demonstrated that rhomboid pseudoprotease Dfm1 is involved in the retrotranslocation of ubiquitinated membrane integral ERAD substrates. Herein, we found that Dfm1 associates with the SPOTS complex, which is composed of serine palmitoyltransferase (SPT) enzymes and accessory components that are critical for catalyzing the first rate‐limiting step of the sphingolipid biosynthesis pathway. Furthermore, Dfm1 employs an ERAD‐independent role for facilitating the ER export and endosome‐ and Golgi‐associated degradation (EGAD) of Orm2, which is a major antagonist of SPT activity. Given that the accumulation of human Orm2 homologs, ORMDLs, is associated with various pathologies, our study serves as a molecular foothold for understanding how dysregulation of sphingolipid metabolism leads to various diseases. Synopsis: Previously, yeast derlin Dfm1 was found to be critical for retrotranslocating integral membrane substrates targeted for ER‐associated degradation (ERAD). This study reveals an ERAD‐independent role for Dfm1 in regulating the degradation of the negative regulator of sphingolipid biosynthesis, Orm2. Dfm1 deletion leads to dysregulated levels of early precursors of the sphingolipid biosynthesis pathway. Derlin Dfm1 associates with rate‐limiting enzymes and regulators of the sphingolipid biosynthesis pathway. Dfm1 targets Ypk1‐dependent phosphorylated Orm2 for ER export and endosome‐ and Golgi‐associated degradation (EGAD). Dfm1's Cdc48‐recruitment function is not required for regulating Orm2 degradation. Abstract : Yeast Dfm1 associates with the SPOTS serine palmitoyltransferase complex and targets its antagonist Orm2 for endosome‐ and Golgi‐associated degradation (EGAD).